Information Infrastructures within European Health Care : Working with the Installed Base - Aanestad, Margunn; Grisot, Miria; Hanseth, Ole; Vassilakopoulou, Polyxeni (Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY-NC 2.5 license. This book consolidates experiences from across Europe on the design, development, implementation and evolution of inter-organisational information infrastructures for healthcare. It provides insights with practical relevance for those involved or interested in the planning and implementation of such infrastructures and includes 11 empirical cases on the introduction of core infrastructural arrangements in different national settings: six cases investigate the use of e-prescriptions and five the public platforms for patient-oriented eHealth services. Both are linked to different types of aims. E-prescription initiatives are usually seen as opportunities to improve healthcare delivery by systematic change (controlling medication costs, improving patient safety and providing rich information for policy making and performance management). Public platforms for patient-oriented eHealth services are seen as opportunities for change and innovation, aiming to strengthen the patients' role and facilitate a shift from provider-centered healthcare towards patient-centeredness. For both types of initiatives, there is a requirement to mix novelty with pre-existing infrastructural components. The cases are analysed by leading experts in health information systems through a common theoretical framework, exploring the role of the pre-existing sociotechnical basis, i.e. the installed base, and how it fundamentally impacts the evolution of information infrastructures. The book advances an "installed base sensitivity" in decision-making both at the policy/strategy level and at the concrete eHealth design level and shows how practitioners and policy-makers can address the complexity of infrastructures that facilitate information flows across organisational boundaries.
Keywords: Medicine.; Health administration.; Health informatics.; Public administration.; elektronické knihy; electronic books